Faculty of Pharmacy UiTM Bertam shares knowledge at Kami Prihatin 8.0 UiTMCP - Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2025)
On the 15th of March 2025, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Cawangan Pulau Pinang (UiTMCPP), participated in the Kami Prihatin 8.0 UiTMCPP: Bertam Berkongsi Berkat! community engagement program held at Masjid At-Taqwa, Taman Bertam Indah, Kepala Batas, Pulau Pinang. This event, led by Dr. Zul-‘Izzat Ikhwan Zaini and officiated by Associate Professor Dr. Kay Dora Abd Ghani (Deputy Rector of PJIM&A), aimed to strengthen ties between UiTM and the local community through knowledge transfer and health awareness activities.